Musée de Grosbois. Hommes et chevaux réunis dans une même saga, celle du Trot - Alain Pagès (In Situ)
It all started with one visionary, Ephrem Houël, an officer from the /Haras nationaux/ (National Studfarms). In 1836, the trotting races were created in Cherbourg city. Following Ephrem Houel’s lead, pioneers created the Société d’Encouragement pour l’Amélioration du Cheval Français in 1864. Let’s not forget the importance of wars, which had a decisive impact on the international expansion of the trotting races "à la française", and the succession of political and administrative events. All these elements were recorded in archives, publications, and written documents recounting the History of this industrious Economy. Their existence led the parent company to open one musée du Trot – Museum of the Trotting Races – in the castle of Grosbois in 2010.